A Review of Research on the Educational Benefits of the Inclusive Model of Education for Special Education Students - Hicks-Monroe, Sherry L. (Journal of the American Academy of Special Education Professionals, 2011)
The practice of inclusion is not a new idea to the educational setting; it is a newer term. Before No Child Left Behind, during the 1970s students with disabilities were mainstreamed into the general education population under Public Law 94-142. Public law 94-142, which was renamed to Individuals with Disabilities Educational Act (IDEA), required students with disabilities to be educated with their non-disabled peers as much as possible. Additionally, IDEA requires that a continuum of placement options be available to meet the needs of students with disabilities. This has not changed with the reauthorization of IDEA 2004, however now students with disabilities must be included in statewide assessment. With this addition to the law, schools are paying more attention to their students with disability populations, thus the emergence of full inclusion. The rationale for inclusion has never rested on research findings alone, but on principle (Hines 2001). Proponents insist that the integration of students with disabilities are inherently right, compared often to the same right to racial integration (Hines, 2001). The primary focus of this article is to review the research on the educational benefits of the inclusive model of education for students with disabilities. The term inclusion or responsible inclusion is a term used to identify the movement to provide service to students with disabilities in the general education setting. Inclusion is usually considered the least restrictive environment for students with disabilities. In this article I will discuss the history of special education, the different services options for educating students with disabilities and the benefits associated with inclusion, as well as the opposing arguments for inclusion.